One Health surveillance approaches for melioidosis and glanders: The Malaysian perspective - Mariappan, Vanitha; Vellasamy, Kumutha Malar; Anpalagar, Rohan Raaj; Lim, Yue-Min; Zainal Abidin, Nurhamimah; Subramaniam, Sreeramanan; Nathan, Sheila (Frontiers in Veterinary Science, 2022)
The One Health concept was initiated to promote integration of human, animal, and environmental ecosystems into healthcare to ensure effective control and the sustainable governance of multifaceted health-matters. Climate change, deforestation, and rigorous farming disrupt environment, which serves as a natural habitat for many animals and microbes, increasing the likelihood of disease transmission between humans and animals. Melioidosis and glanders are diseases of humans and animals caused by the gram-negative bacteria Burkholderia pseudomallei and its close relative Burkholderia mallei, respectively. In Malaysia, although melioidosis is endemic, it is not a notifiable disease. Hence, true prevalence of melioidosis in Malaysia is unknown. To date, no incidence of human glanders has been reported in Malaysia, although occupational exposure for equine handlers and veterinary professionals remains a concern. Additionally, antibiotics are widely used in the healthcare and veterinary sectors to treat or prevent B. pseudomallei and B. mallei infections, leading to the emergence of resistance in B. pseudomallei. Lack of surveillance, research, assessment, and management of glanders and melioidosis is a major issue in Malaysia. Proper assessment systems and cross-discipline cooperation are vital to recognise and manage both diseases. Experts and practitioners from clinical and veterinary disciplines, environmentalists, law enforcement, policymakers, researchers, local communities, and other experts need to communicate, collaborate, and coordinate activities to fill the knowledge gap on glanders and melioidosis to reduce morbidity and mortality rates. This review aims to define the organisational and functional characteristics of One Health surveillance approaches for glanders and melioidosis from a Malaysian perspective.